Upstream horizontal mergers and efficiency gains - Chrysovalantou Milliou; Apostolis Pavlou (Center for Economic Studies and ifo Institute (CESifo), 2009)
We study upstream horizontal mergers and their potential efficiency gains. We show that an upstream horizontal merger can give rise to two efficiency-enhancing effects when firms trade through two-part tariffs. It increases R&D investments and decreases wholesale prices when downstream competition is not too strong. Examining whether the merger's potential efficiency gains can overcome its anti-competitive effects in terms of welfare, we show that when firms merge usually both of the above mentioned efficiencies are realized and they are passed on to consumers. This holds to a lesser extend when firms trade through linear contracts.
Keywords: L41; L42; L22; 330; horizontal mergers; vertical relations; efficiency gains; two-part tariffs; merger policy